The Expression and Prognostic Impact of Immune Cytolytic Activity-Related Markers in Human Malignancies: A Comprehensive Meta-analysis - Roufas, Constantinos; Chasiotis, Dimitrios; Makris, Anestis; Efstathiades, Christodoulos; Dimopoulos, Christos; Zaravinos, Apostolos (Frontiers in Oncology, 2018)
Background: Immune checkpoint blockade has shown striking clinical results in different cancer patients. However, a significant inter-individual and inter-tumor variability exists among different cancers. The expression of GZMA and PRF1, secreted by effector cytotoxic T-cells (CTL) and natural killer (NK) cells, were recently used as a denominator of the intratumoral immune cytolytic activity. Although their levels are significantly elevated upon CD8+ T-cell activation and during a productive clinical response against immune checkpoint blockade therapies, it is not completely understood how different tumors induce and adapt to immune responses. Methods: We calculated the cytolytic activity (CYT) across different cancer types and focused on differences between primary and metastatic tumors. We screened the variation of CYT across 32 different cancer types and correlated CYT with the corresponding patient group’s overall survival, the expression of several immune checkpoint molecules, as well as with the TIL and TAN load in these tumors. Results: We found diverse levels of CYT across different cancer types, with highest levels in kidney, lung, and cervical cancers, and lowest levels in glioma, adrenocortical carcinoma, and uveal melanoma. GZMA and PRF1 protein levels from tissue microarrays from 20 different tumor types validated the gene expression results. CYT was significantly higher in metastatic melanoma and correlated significantly to the TIL load. In adrenocortical carcinoma, skin melanoma and bladder cancer, CYT was associated with an improved patient outcome and high levels of both genes synergistically affected patient survival in these cancers. In bladder, breast, colon, esophageal, kidney, ovarian, pancreatic, testicular and thyroid cancers, high CYT was accompanied by upregulation of at least one immune-checkpoint inhibitor, indicating that similar to melanoma and prostate cancer, immune response in CYT-high tumors elicit immune suppression in the tumor microenvironment. Conclusions: Overall, our data highlight the existence of diverse levels of CYT across different cancer types and suggest that along with the existence of complicated associations among various tumor-infiltrated immune cells, it is capable to promote or inhibit the establishment of a permissive tumor microenvironment, depending on the type of cancer. High levels of immunosuppression seem to exist in several tumor types.